Novel Gene Clusters for Secondary Metabolite Synthesis in Mesophotic Sponge‐Associated Bacteria - Nuo Chen; Liwei Liu; Jingxuan Wang; Deqiang Mao; Hongmei Lu; Tânia Keiko Shishido; Shuai Zhi; Hua Chen; Shan He (Microbial Biotechnology)
ABSTRACT Mesophotic coral ecosystems (MCEs) host a diverse array of sponge species, which represent a promising source of bioactive compounds. Increasing evidence suggests that sponge‐associated bacteria may be the primary producers of these compounds. However, cultivating these bacteria under laboratory conditions remains a significant challenge. To investigate the rich resource of bioactive compounds synthesised by mesophotic sponge‐associated bacteria, we retrieved 429 metagenome‐assembled genomes (MAGs) from 15 mesophotic sponges, revealing a strong correlation between bacterial diversity and sponge species. Furthermore, we identified 1637 secondary metabolite biosynthetic gene clusters (BGCs) within these MAGs. Among the identified BGCs, terpenes were the most abundant (495), followed by 369 polyketide synthases (PKSs), 293 ribosomally synthesised and post‐translationally modified peptides (RiPPs) and 135 nonribosomal peptide synthetases (NRPSs). The BGCs were classified into 1086 gene cluster families (GCFs) based on sequence similarity. Notably, only five GCFs included experimentally validated reference BGCs from the Minimum Information about a Biosynthetic Gene cluster database (MIBiG). Additionally, an unusual abundance of BGCs was detected in Entotheonella sp. (s191209.Bin93) from the Tectomicrobia phylum. In contrast, members of Proteobacteria and Acidobacteriota harboured fewer BGCs (6–7 on average), yet their high abundance in MCE sponges suggests a potentially rich reservoir of BGCs. Analysis of the BGC distribution patterns revealed that a subset of BGCs, including terpene GCFs (FAM_00447 and FAM_01046), PKS GCF (FAM_00235), and RiPPs GCF (FAM_01143), were widespread across mesophotic sponges. Furthermore, 32 GCFs were consistently present in the same MAGs across different sponges, highlighting their potential key biological roles and capacity to yield novel bioactive compounds. This study not only underscores the untapped potential of mesophotic sponge‐associated bacteria as a source of bioactive compounds but also provides valuable insights into the intricate interactions between sponges and their symbiotic microbial communities.